Reparation For Unlawful Expropriation Of Foreign Investment Under International Law - Abdalhade Mossa Rshda; Norfadhilah Mohamad Ali; Fadhlina Alias (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
This descriptive paper discusses the issue of reparation for unlawful expropriation of foreign investment, which is considered one of the most controversial areas in international law. many scholars point out that the Public purpose, non-discriminatory basis, due process of law, obligation not to infringement any prior contractual obligation, and payment of compensation, are the main conditions that commonly set for the legality of an expropriation by international law. The expropriation should be achieving this primary conditions of conduct to be considered as lawful expropriation. If the State fails to meet such preconditions the expropriation becomes unlawful and it entails the international responsibility of the State. While there is no general debate in customary law at the present time about the state's obligation to compensate for expropriation of foreign investment, where it's under customary international law, when a state breaches its obligations or exercises its power in a way that deprives a party of its property, that party is entitled to one of the following forms of reparation: restitution, compensation or satisfaction. what is the concept of unlawful expropriation of foreign investment? When the expropriation considered unlawful? what is the forms of reparation? what is the position of BITs and arbitral tribunals from the reparation for unlawful expropriation? These are important questions should be answered in a sequential methodology manner. Only by figuring out the answers of these important questions and making references to former arbitral tribunals decisions can we understanding the reparation for unlawful expropriation and its forms